Motorcycle-to-car ownership at different urbanization levels: road mobility, accessibility, and income inequality - Law, Teik Hua; Ng, Choy Peng; Poi, Alvin Wai Hoong; Guo, Baohua; Hu, Qizhou (Elsevier, 2023)
Recent empirical research found that the motorcycle-to-car (MTC) ownership ratio and economic performance have an inverse U-shaped relationship, with the MTC ownership ratio increasing at lower economic levels but decreasing after a critical threshold. This study examined the effects of income per population, relative improvements in road mobility over road accessibility (MOA) and income inequality on the MTC ownership ratio under different levels of urbanization. A panel of 53 nations from 1963 to 2013 was analyzed using fixed-effects panel linear regression. The inverse U-shaped relationship between the MTC ownership ratio and income changes to a U-shaped relationship as urbanization rises. The growing rate of the MTC ownership ratio and the turning point for the inverse U-shaped relationship between the ratio and income inequality both rise along with urbanization. The negative effect of MOA on the ownership ratio of MTC is lessened by urbanization.